Thinking Outside the Boxcar: Effective and Sustainable Combined Remedies Using Single Application of Multifunctional Amendments. Issue 1 (9th January 2017) - Burns, Matthew; Carstens, David; Ghosh, Emily; Lewis, Richard; Zajdlik, Jason; Bakenne, Ademola M.; De Tilly, Robert Noel
Abstract: The combined remedy approach to groundwater remediation optimizes contaminated site cleanup as measured by technical efficacy and sustainability. Regardless of the potential for improving site cleanups, there are several obstacles limiting the implementation of combined remedies. The obstacles primarily stem from an inability of liability owners to easily determine if economic costs are synergistic or additive and from regulatory hesitancy to codify needed timing and technology sequencing flexibility within design documents. These obstacles can often be circumvented by employing multicomponent and multifunctional remedial amendment formulations delivered with a single application. Case studies are presented that demonstrate efficacy of this combined remedies approach. The sustainability of the approach is also assessed by evaluation of economic viability, social productivity, and environmental protection. The case studies include combined abiotic and biotic degradation of chlorinated ethene and ethane compounds, combined reductive, and microaerophilic treatment of chlorinated benzenes, and combined chemical oxidation and biodegradation of petroleum compounds. Case studies are supported with conventional concentration trends and advanced diagnostics including compound specific isotope analysis (CSIA) and genetic‐based molecular biological tools (MBTs).